Clinical Impacts of Cyp3a4 Isoenzyme on Drugs Used in Treatment of Cardiovascular Diseases: Drug-Drug Interactions - Macit, Caglar; Taner, Neda; Ozbay, Latif; Behzetoglu, Yuksel; Mercanoglu, Guldem (Cardiology and Cardiovascular Medicine, 2016)
There are plenty of factors that change the clinical impacts of drugs. Some of them are genetic, physiological and drug-drug interactions. However, drug-drug interaction is the preliminary factor because of the drugs’ relationship with CYP family, especially with CYP3A4. The objective of this study is to discuss the effect of CYP3A4 dependent drug interactions about cardiovascular drugs. In this paper, a literature search was performed using PubMed, MEDLINE, Web of Science, and the Cochrane Library to analyze the pharmacokinetic drug-drug interactions associated with CYP3A4 isoenzyme. As a result, we showed the importance of drug-drug interaction related to CYP3A4 isoenzyme that has an affect on drugs used in cardiovascular diseases. In conclusion, although we found lots of drug-drug interactions related to CYP3A4 isoenzyme on cardiovascular drugs, future studies should be done for exact information about this topic.